Self-employment and covid-19: A conceptual study - Siti Noraain M.Hamdan; Beatrice Lim Fui Yee; Roslinah Mahmud; Noor Faziedah Chun Li @ Mohd Fadzlee (Universiti Malaysia Sabah, 2021)
The COVID-19 pandemic has spread with alarming speed, infecting millions and bringing economic activity to a near-standstill as countries imposed tight restrictions on movement to halt the spread of the virus. Coronavirus outbreak will have devastating effects on the Malaysian economy from both external factors which are global supply and demand shocks and domestic factors of Movement Control Order (Calvin Cheng, 2020). Critically, this will disproportionately impact smaller businesses and vulnerable groups such as lower-income individuals and self-employed. As the health and human toll grows, the economic damage is already evident and represents the largest economic shock the world has experienced in decades. As for now, it is clear that this pandemic will have intensely damaging effects on both the Malaysian micro and macro economy as well as on the economic welfare of the society. This article analyses the effects of COVID-19 on self-employed individuals and the policies of government in order to help vulnerable groups such as lower-income individuals and self-employed and recover the economy due to impact of COVID-19. In the case of business scenario, COVID-19 has impacted most of the small businesses significantly compare to large firms. MCO causes most of the small businesses operators to temporarily shut down their activities to contain the spread of this virus. The findings from this study is expected to enhance the understanding of the operations of small businesses and their potential and benefits. In addition, those businesses can identify factors that benefit small enterprise to reduce the massive impact of this pandemic to ensure sustainability in the future.